INTERNALISASI FILOSOFI BUDAYA SUMATERA UTARA MELALUI KARYA MURAL UNTUK MENUMBUHKAN APRESIASI TERHADAP KEBERAGAMAN BUDAYA INDONESIA PADA ANAK USIA DINI - Muslim; Raden Burhan Surya Natadiningrat; Mesra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Indonesia is a multicultural nation whose cultural diversity constitutes both a national identity and an important foundation for character education. Nevertheless, cultural learning in Early Childhood Education (ECE) is still predominantly delivered through conventional approaches that have not fully facilitated the internalization of the philosophical values embedded in local cultures. This study aimed to describe the process of internalizing the cultural philosophy of North Sumatra through mural artwork to foster children's appreciation of Indonesia's cultural diversity. A descriptive qualitative approach was employed at PAUD Balqis. Data were collected through classroom observations, interviews with teachers, and documentation of mural-based learning activities. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing, while data credibility was ensured through source and technique triangulation. The findings reveal that the murals represent North Sumatran cultural philosophy through illustrations of traditional houses, traditional costumes, children's figures, and cultural landscapes that embody the values of togetherness, mutual cooperation, tolerance, respect, and social harmony. The internalization process occurred through observation, guided interpretation, and the contextualization of cultural values into children's daily experiences. Observation, interview, and documentation data further indicate that mural-based learning encouraged children's appreciation of Indonesia's cultural diversity, reflected in their increased curiosity about cultural differences, improved ability to recognize diverse cultural identities, and growing attitudes of respect toward diversity. These findings demonstrate that mural artwork grounded in local cultural philosophy can serve as an effective contextual learning medium for strengthening multicultural character education in early childhood.